Ileal fecaloma in a 2-month healthy boy - Alhariqi, Bader A; Alamri, Nasser; Bedewi, Mohammed; Aldossari, Khaled K (Indian Journal of Case Reports, 2024)
A fecaloma is a fecal matter that builds up to form a hard mass of feces that is extremely rigid than a mass connected with fecal impaction. Fecalomas are commonly in the rectosigmoid region. Our report aimed to give a brief review of this case and discuss the treatment options for it. A 2-month-old male presented with bowel obstruction and a palpable mass on the right side of the abdomen. A simple abdominal radiograph and contrasted abdominal computed tomography scan were performed immediately, resulting in small intestine mechanical obstruction. A 4.6 × 6.6 × 4 cm fecaloma was found in the distal ileum. We consequently diagnosed a case of ileal fecaloma-producing small bowel obstruction. The patient was surgically managed after conservative treatment failed.